Real-Time Precise Point Positioning in NAD83: Global and Regional Broadcast Corrections Compared - Teunissen, Peter; Huisman, L.; Hu, C. (American Society of Civil Engineers, 2013)
Real-time precise point positioning (PPP) is possible through the availability of the real-time satellite orbit and clock corrections to broadcast ephemeris, the real-time broadcast corrections (BCs). The real-time BCs are currently available in global as well as in regional reference frames. In this contribution, PPP usage and the performance of these global and regional BCs are analyzed for the North American Datum of 1983 (NAD83). The limitations of the current regional BC approach for NAD83 are identified and the coordinate differences it leads to compared with the traditional global BC approach are shown. Although the biases as a result of the different reference frame usage are shown to be subcentimeter, it is also shown how they can be reduced or eliminated by modifying either the PPP algorithm or the regional BC approach. Analyses were performed for three different PPP variants, a single-frequency ionosphere-free variant, a dual-frequency ionosphere-free variant, and a single-frequency ionosphere-corrected variant.